Vibrational Spectroscopic Investigation of 2,2 '-Bipyridine Adsorbed on Loughlinite from Aqueous Suspensions - AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Asian Journal Of Chemistry, 11/100 Rajendra Nagar, Sector 3,, Sahibabad 201 005, Ghaziabad, India, 2010)
The adsorption of 2,2'-bipyridine onto loughlinite (Na-sepiolite) has been investigated by FT-IR and micro-Raman spectroscopy. Spectroscopic results indicate the formation of monoanionic surface species. Most of the adsorbed molecules are incorporated in the channels of the clay structure and coordinated to Lewis acidic centers directly or indirectly through water molecules.
Keywords: clays; Infrared and Raman spectra; 2,2'-Bipyridine; loughlinite; Sepiolite; Vibrational frequencies; transition-metal-complexes; raman-spectra; na-sepiolite; FT-IR; adsorption; pyridine; cyclohexylamine; luminescent; desorption; anatolia; killer; Infrared ve Raman spektrumları; titreşim frekansları; geçiş metali kompleksleri; desorpsiyon; Anadolu